2020
DOI: 10.1080/20002297.2020.1820834
|View full text |Cite
|
Sign up to set email alerts
|

Interaction between genetic factors, Porphyromonas gingivalis and microglia to promote Alzheimer’s disease

Abstract: In late-onset Alzheimer disease (AD) pathogenesis, genes, infections and immunity could be significant factors. We have reviewed if the keystone periodontal pathogen Porphyromonas gingivalis may affect genes and microglia (primary immune cells in the brain) to promote AD development. Genes for apolipoprotein, clusterin, CD33, triggering receptor expressed on myeloid cells-2 (TREM-2), tyrosine kinase binding protein (TYR-OBP), and complement receptors can affect microglia. Most of these genes can also be affect… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

0
21
0
2

Year Published

2020
2020
2024
2024

Publication Types

Select...
8
1

Relationship

5
4

Authors

Journals

citations
Cited by 25 publications
(23 citation statements)
references
References 86 publications
(146 reference statements)
0
21
0
2
Order By: Relevance
“…Periodontitis can exert its influence indirectly by sustaining peripheral inflammation. This together with defective susceptibility genes that normally help with clearance of waste from the brain, can prime microglial cells into a pro-inflammatory phenotype [ 20 ].…”
Section: What Makes P Gingivalis a Risk Factor Fomentioning
confidence: 99%
“…Periodontitis can exert its influence indirectly by sustaining peripheral inflammation. This together with defective susceptibility genes that normally help with clearance of waste from the brain, can prime microglial cells into a pro-inflammatory phenotype [ 20 ].…”
Section: What Makes P Gingivalis a Risk Factor Fomentioning
confidence: 99%
“…The interaction between genetic factors, microglia, and P. gingivalis was reviewed by Olsen and Singhrao (2020) . It was suggested that genes for apolipoprotein, clusterin, CD33, triggering receptor expressed on myeloid cells-2, tyrosine kinase binding protein (TYR-OBP), and complement receptors could affect microglia.…”
Section: Microglia and Porphyromonas Gingivalismentioning
confidence: 99%
“…Depending on the trigger of activation, M1 can exert cytotoxic (pro-inflammatory cytokine release) and M2 neuroprotective (immune resolution) effects [52]. The chronic nature of low-level infections such as gingivitis/periodontitis and associated by products, e.g., endo/exotoxins and cytokines could affect the capacity of susceptible brains' defense to a point where microglia, "remembering" previous P. gingivalis exposure, turn into the M1 phase [50,53].…”
Section: Amyloid-␤ Occurs In the Brain Of Both Healthy And Ad Peoplementioning
confidence: 99%
“…It is also possible that Aβ in healthy older people gradually contributes to neuroinflammation and neurodegeneration when microglia activation develops as a protective response to P. gingivalis [ 50 ]. Microglia have a dual role in the pathogenesis of AD.…”
Section: Amyloid-β Occurs In the Brain Of Both Healthy And Ad Peoplementioning
confidence: 99%